Analysis of Peruvian immigrants in Berlin and cultural ruptures in the labor aspect - P. J. Pazos (Ибероамериканские тетради)
The phenomenon of mobility in Peru has defined a particular worldview of the Peruvian people, manifested in the distinction between work and the state. The gender approach is especially important in relation to German state subsidies, whereas state benefits or lack of access to them has become a criterion of stigmatization. The lives of those Peruvians who have been able to adapt in one way or another to working life in Berlin are markedly different. Through their work, Peruvians have been able to gain the trust of many Germans, and to gain the appreciation and respect of their Peruvian and Latin American compatriots, in fact, prestige. In this context, however, it must also be understood that it is the new way of life, which also involves work and daily activities, that brings confrontation between blood relatives and families, generating deep ruptures.